2023
DOI: 10.3389/fimmu.2023.1287182
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous device-free islet transplantation

Xudong Zhou,
Zhiran Xu,
Yanqiu You
et al.

Abstract: Diabetes mellitus is a chronic metabolic disease, characterized by high blood sugar levels; it affects more than 500 million individuals worldwide. Type 1 diabetes mellitus (T1DM) is results from insufficient insulin secretion by islets; its treatment requires lifelong use of insulin injections, which leads to a large economic burden on patients. Islet transplantation may be a promising effective treatment for T1DM. Clinically, this process currently involves directly infusing islet cells into the hepatic port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…Moreover, uncertainties surround the effectiveness and safety of biomaterials used to encapsulate artificial islets created from stem cells, with concerns about post-implantation transdifferentiation, teratoma formation, or graft migration requiring careful consideration. To enhance the long-term efficacy and safety of islet cell treatment for diabetes patients, efforts must concentrate on improving islet graft survival and functionality in highly vascularized, nutrient-and oxygen-rich environments [56].…”
Section: Pancreatic Islet Cell Transplantationmentioning
confidence: 99%
“…Moreover, uncertainties surround the effectiveness and safety of biomaterials used to encapsulate artificial islets created from stem cells, with concerns about post-implantation transdifferentiation, teratoma formation, or graft migration requiring careful consideration. To enhance the long-term efficacy and safety of islet cell treatment for diabetes patients, efforts must concentrate on improving islet graft survival and functionality in highly vascularized, nutrient-and oxygen-rich environments [56].…”
Section: Pancreatic Islet Cell Transplantationmentioning
confidence: 99%
“…Subcutaneous transplantation of islets is simple and easy to monitor and poses low complication risk 86 . However, the lack of vascularization in the subcutaneous space hinders the supply of nutrients and oxygen, influencing the effect of grafts.…”
Section: Sites For Islets/mscs Co-transplantationmentioning
confidence: 99%
“…The results indicated that both the BMSC–islet and EMSC–islet composites significantly reduced fragmentation and increased islet mass in porcine pancreatic islets alone. Finally, in a prevascularized deviceless (DL) subcutaneous transplantation method, ADMSCs and islet cells were colocalized in the subcutaneous spaces 86 . The DL subcutaneous space was prepared by implanting a nylon catheter under the skin of mice and then transplanting islets and ADMSCs that had been co-cultured for 24 h into the DL subcutaneous space or renal capsule, which demonstrated that DL subcutaneous space in combination with ADMSCs achieved euglycemia 11 weeks after transplantation but prevented deleterious graft fibrosis overgrowth 89 .…”
Section: Sites For Islets/mscs Co-transplantationmentioning
confidence: 99%